2013
DOI: 10.4236/ojsta.2013.22008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some <i>N</i>-[(4-Substituted-1-Piperazinyl)-Oxo(Alkyl and Ethylcarbamoyl)]-3-(2-Thiophenyl)Acrylamides as Non-Steroidal Anti-Allergic and Anti-Inflammatory Agents

Abstract: An interesting approach for the design of anti-allergies is rationally considered. It was proved that current anti-allergic drugs comprise piperazine and acrylic acid segments. In harmony with these findings, new products 5a-u were synthesized starting from conjugated 2-thiopheneacrylic acid with amino acid esters 3a-g followed by coupling of their acid derivatives 4a-g with some piperazine segments, with the aim to increase their biological activities and decrease side effects. The anti-allergic and anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Particularly, the compound 2-acetylthiophene-2-hydroxy-3-methoxybenzohydrazone monohydrate, previously named o-HVATPNNH and hereafter referred to as H 2 L, has been previously synthesized and structurally characterized [24] and has the conditions of an effective ligand. The precursors used to obtain the ligand were selected taking into account that (i) o-vanillin (3-methoxysalicilaldehyde or 2-hydroxy-3-methoxybenzaldehyde) showed antioxidant activity, low toxicity and strong tendency to combine with amine derivatives, generating stable ligands [23,25,26], and that (ii) thiophene (five-membered heterocyclic with sulfur as the heteroatom) and its derivatives have been widely studied for their therapeutic applications [27,28], showing good results as anti-tumor agents [29,30], analgesic and anti-inflammatory [31], anti-hypertensive [32], anti-diabetic [33], cholesterol activity inhibitors [34], anti-allergenic [35] and antioxidant agents [36], constituting a group of compounds of both pharmacological and agrochemical interest for their bactericidal, fungicidal and herbicidal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the compound 2-acetylthiophene-2-hydroxy-3-methoxybenzohydrazone monohydrate, previously named o-HVATPNNH and hereafter referred to as H 2 L, has been previously synthesized and structurally characterized [24] and has the conditions of an effective ligand. The precursors used to obtain the ligand were selected taking into account that (i) o-vanillin (3-methoxysalicilaldehyde or 2-hydroxy-3-methoxybenzaldehyde) showed antioxidant activity, low toxicity and strong tendency to combine with amine derivatives, generating stable ligands [23,25,26], and that (ii) thiophene (five-membered heterocyclic with sulfur as the heteroatom) and its derivatives have been widely studied for their therapeutic applications [27,28], showing good results as anti-tumor agents [29,30], analgesic and anti-inflammatory [31], anti-hypertensive [32], anti-diabetic [33], cholesterol activity inhibitors [34], anti-allergenic [35] and antioxidant agents [36], constituting a group of compounds of both pharmacological and agrochemical interest for their bactericidal, fungicidal and herbicidal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work (14) reported that some of the β-aryl and βheteroarylacrylamides conjugated with amino acid, peptide and piprazinyl group displayed a markedly high anti-allergic activity.…”
mentioning
confidence: 99%